Impact of enzyme replacement therapy and migalastat on left atrial strain and cardiomyopathy in patients with Fabry disease - Pogoda, Christian; Brand, Stefan-Martin; Duning, Thomas; Schmidt-Pogoda, Antje; Sindermann, Jürgen; Lenders, Malte; Brand, Eva (Frontiers in Cardiovascular Medicine, 2023)
Aims Cardiomyopathy in Fabry disease (FD) is a major determinant of morbidity and mortality. This study investigates the effects of FD-specific treatment using enzyme replacement therapy (ERT) and chaperone therapy on left atrial (LA) function using two-dimensional speckle tracking echocardiography (2DSTE). Methods and results In this prospective observational single-center study, 20 FD patients [10 (50%) females] treated with migalastat, 48 FD patients [24 (50%) females] treated with ERT (agalsidase-alfa and agalsidase-beta), and 30 untreated FD patients (all females) as controls were analyzed. The mean follow-up time ranged from 26 to 81 months. 2DSTE was performed for left ventricle strain, right ventricle strain, and LA strain (LAS). FD-specific treated patients presented with increased left ventricular mass index (LVMi) and higher frequency of left ventricular hypertrophy at baseline, whereas untreated control patients showed normal baseline values. FD-specific treated (including migalastat and ERT) patients showed stabilization of LAS over time (p > 0.05). LVMi was also stable in treated FD patients during observation (p > 0.05). Conclusion In patients with FD, treated with either ERT or chaperone therapy, LAS values measured by echocardiographic speckle tracking were stable over time, pointing toward disease stabilization.